2018
DOI: 10.18203/2394-6040.ijcmph20180505
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors influencing anaemia among urban adolescent females, a cross sectional study

Abstract: Background: Despite many organized efforts by the government, adolescent anemia remains to be a major public health problem in India. The prevalence of anemia and factors influencing it in urban adolescent females is a relatively less studied aspect. Hence the current study is conducted with an objective of assessing the prevalence and factors influencing anemia among adolescent school girls living in an urban locality. Methods: The current study was a community-based cross sectional study conducted in the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
5
1
1
Order By: Relevance
“…7 In our study, the maximum number of patients were from 21-40 years of age (65.3%). This is in accordance with study conducted by Poyyamozhi et al 8 In our study, we have observed that most of the patients presented with tinea cruries et corporis (86.6%), followed by tinea cruris et corporis et faciei (8.9%) and tinea corporis et cruris (4.4%). Interestingly, among the current study population, tinea faciei was seen in adults patients, a location which has been described in children, and almost invariably this presentation could be because of over the counter topical steroid abuse.…”
Section: Resultssupporting
confidence: 93%
“…7 In our study, the maximum number of patients were from 21-40 years of age (65.3%). This is in accordance with study conducted by Poyyamozhi et al 8 In our study, we have observed that most of the patients presented with tinea cruries et corporis (86.6%), followed by tinea cruris et corporis et faciei (8.9%) and tinea corporis et cruris (4.4%). Interestingly, among the current study population, tinea faciei was seen in adults patients, a location which has been described in children, and almost invariably this presentation could be because of over the counter topical steroid abuse.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained in studies conducted by Mandot and Bamnawat, Poyyamozhi et al ., Melwani et al ., Soman et al ., where the prevalence rates were found to be 41.1%, 62%, 67.77%, and 83.6% respectively. [ 9 18 19 20 ] Any developing nation, which has a prevalence of anemia more than 40%, is categorized as of severe public health significance. [ 21 ] This shows that the burden of anemia is very high among adolescent girls and it poses a major public health problem and interventions have to be carried out to improve their overall health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…While Biradar et al [23] reported more anaemia prevalence among girls above 14 years of age in comparison to those below 14 years. Talan [24] in their study among 500 adolescent girls (10-19 years) of Uttar Pradesh, India found higher prevalence of anaemia among early adolescents (65.7%) as compared [29]. Number of children in the family was also found associated with anaemia, as greater the numbers of children in the family greater the demand for foods and poor the quality of care, that implies greater risk of anaemia [30].…”
Section: Discussionmentioning
confidence: 99%